2016
DOI: 10.1111/jipb.12466
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the gene encoding 1‐aminocyclopropane‐1‐carboxylate synthase 4 (CitACS4) led to andromonoecy in watermelon

Abstract: Although it has been reported previously that ethylene plays a critical role in sex determination in cucurbit species, how the andromonoecy that carries both the male and hermaphroditic flowers is determined in watermelon is still unknown. Here we showed that the watermelon gene 1-aminocyclopropane-1-carboxylate synthase 4 (CitACS4), expressed specifically in carpel primordia, determines the andromonoecy in watermelon. Among four single nucleotide polymorphism (SNPs) and one InDel identified in the coding regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…In this study, as shown by the DEGs depicted in Table S5, the ethylene biosynthesis gene ACS was upregulated in the gynoecious lines. This result supports prior studies indicating that CitAC4 (Cla011230) is a key gene required for stamen arrest during female flower development in watermelon (Ji et al, 2016;Manzano et al, 2016). We noticed that three notably upregulated genes in the gynoecious lines were associated with cytokinin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, as shown by the DEGs depicted in Table S5, the ethylene biosynthesis gene ACS was upregulated in the gynoecious lines. This result supports prior studies indicating that CitAC4 (Cla011230) is a key gene required for stamen arrest during female flower development in watermelon (Ji et al, 2016;Manzano et al, 2016). We noticed that three notably upregulated genes in the gynoecious lines were associated with cytokinin.…”
Section: Discussionsupporting
confidence: 92%
“…The proposed genotype for each of the six sex forms in watermelon is as follows: monoecious (A_Gy_Tm), trimonoecious (A_Gy_tmtm), andromonoecious (aaGy_Tm_ or aaGy_tmtm), gynoecious (A_gygyTm_), gynomonoecious (A_gygytmtm) and hermaphrodite (aagygyTm_ or aagygytmtm) (Ji et al, 2015). The a locus has been identified and encodes a 1-aminocyclopropane-1-carboxylic synthase (ACS) gene CitACS4 (Boualem et al, 2016;Ji et al, 2016;Manzano et al, 2016). The enzyme ACS is important in the ethylene biosynthesis pathway, and an activity-reduced mutation, C364W, within its conserved region led to andromonoecy from monoecy in watermelon (Ji et al, 2016;Manzano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By taking into account the andromonoecious index (AI) (Martıńez et al, 2014), as well as studying the sex phenotypes of these control lines, more than 200 C. lanatus accessions were separated into three sex phenotypic classes: monoecious (plants with AI=1-1.35), partially andromonoecious (plants with AI=1.35-2.7), and andromonoecious (plants with AI=2.7-3). It has been reported that andromonoecy phenotype is caused by the CitACS4 mutant allele m (Boualem et al, 2016;Ji et al, 2016;Manzano et al, 2016), although is also responsible for PA under heterozygous conditions. So, MM and mm plants are monoecious and andromonoecious, respectively, while Mm are PA, with AI ranging from 1.35 to 2.7 (Manzano et al, 2016).…”
Section: Partial Andromonoecious Phenotype Is Conferred By a Single Rmentioning
confidence: 99%